2019
DOI: 10.15625/0866-7187/41/4/14233
|View full text |Cite
|
Sign up to set email alerts
|

Seismogenic nodes as a viable alternative to seismogenic zones and observed seismicity for the definition of seismic hazard at regional scale

Abstract: It is shown that considering a fixed increment of a given magnitude at a fault is equivalent to factoring the mechanical moment at the fault as done in structural engineering with the applied loads, by the most currently used structural engineering standards (e.g. Eurocodes). A special safety factor gEM is introduced and related to the partial factor gq acting on the mechanical moment representing the fault.A comparison is then made between the hazard maps obtained with the Neo Deterministic Seismic Hazard Ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…According to this classification, low hazard suggests the possibility of Note: Δ = n D − n N events with magnitudes M4-4.9, while moderate hazard suggests the possibility of events with magnitudes 5-5.9. The results obtained generally do not contradict the seismic history of the study region and can be helpful for long-term seismic hazard assessment in the Corsica-Sardinia region (Rugarli et al 2019). The information about the possible locations of M5+ earthquakes fills possible gaps in known seismicity.…”
Section: Conclusion and Discussionmentioning
confidence: 54%
“…According to this classification, low hazard suggests the possibility of Note: Δ = n D − n N events with magnitudes M4-4.9, while moderate hazard suggests the possibility of events with magnitudes 5-5.9. The results obtained generally do not contradict the seismic history of the study region and can be helpful for long-term seismic hazard assessment in the Corsica-Sardinia region (Rugarli et al 2019). The information about the possible locations of M5+ earthquakes fills possible gaps in known seismicity.…”
Section: Conclusion and Discussionmentioning
confidence: 54%
“…Namely, we added a safety increment ΔM= EM M to the maximum magnitude observed or estimated for the nodes (with pattern recognition of morphostructural zonation), where EM (here set to 2.0) is a tunable safety factor and M (here set to 0.25) is a value representative of the global uncertainty on magnitude determination (Båth, 1973). Rugarli et al (2019b) demonstrated that the application of this increment to the lower bound magnitude of seismogenic nodes in Italy returns hazard levels that envelope or match the 1000-years long Italian earthquake catalogue almost everywhere. They showed that the application of this ΔM increment is equivalent to applying a partial safety factor q to the seismic moment at the fault M 0 , as normally asked by Eurocodes and other international standards for typical structural design.…”
Section: Resultsmentioning
confidence: 98%
“…Since by definition seismogenic nodes, which can be identified by pattern recognition via morphostructural zonation (MZ), per Gorshkov et al (2003) -accommodate earthquakes with a magnitude above a fixed threshold M (Gorshkov et al, 2002;Peresan et al, 2015;Gvishiani et al, 2020) therefore their use is recommended in the NDSHA procedure whenever either historical parametric catalogues are unavailable or, although available, they cannot be considered sufficiently complete. A comprehensive validation of seismogenic nodes as a viable alternative to both seismogenic zones and observed seismicity, for the definition of seismic hazard at regional scale, is given by Rugarli et al (2019b).…”
Section: Methodsmentioning
confidence: 99%
“…In an important recent finding, Rugarli et al (2019b) have shown, using the unique 1000 + years" catalogue available for Italy, that seismogenic nodes may represent a viable alternative to seismogenic zones and observed seismicity for the reliable definition of seismic hazard at regional scale. Their paper provides both a validation of the seismogenic nodes method, and it also further supplies a tentative tuning of the safety factor γ EM at about ≈ 2.…”
Section: "One Must Never Say Anything Too Specific About Earthquakes" -Perry Byerlymentioning
confidence: 99%
See 1 more Smart Citation